Analisis Beberapa Faktor Yang Mempengaruhi Loyalitas Nasabah Pd.Bkk Eromoko Kantor Cabang Nguntoronadi - Sari, Harlina Fitriani; , Drs. Kusdiyanto, S.E., M.Si (2016)
The aim of this study was to determine some of the factors that affect customer loyalty in Pd. Bkk Eromoko Branch Office Nguntoronadi in terms of the factors that influence quality of service, customer confidence, and facilities. Based on the results of the study are expected to provide inputs or information for the company to be used as consideration in an effort to improve or develop customer loyalty. This study is a survey research with a quantitative approach. Tests were performed in this study using a test instrument that research validity and reliability test, test the classical assumption of normalistas test, test the hypothesis that multiple linear regression, t test, F test and coefficient of determination or R2. The data in this study are primary data obtained by distributing questionnaires to respondents, where respondents here are customers Pd. Bkk Eromoko Branch Office Nguntoronadi. Samples taken in the study of 100 customers Based on t test variable quality of service (X1) has a significant influence on customer loyalty can be proved that the p-value of 0.000 is greater than p-α by 0,05.Variabel customer confidence (X2) have a significant influence on customer loyalty variables can be proved by the results of p-value of 0.039 is smaller than α p-value of 0.05. While variable Facility (X3) has a significant influence on customer loyalty can be evidenced by the results of the p-value of 0.000 magnitudes of p-α by 0,05. F test indicates that there is a simultaneous effect between variables Customer trust, quality of service, and facilities on customer loyalty as evidenced by the amount calculated F value of 47.701 with a p-value 0.000 level smaller than the p-α 0.05 Results of the coefficient of determination (R ²) shows that the value of 0.598. This means that 32.9% can be explained by the variable satisfaction, trust and commitment, while the remaining 67.1% is influenced by other variables. Keywords: service quality, customer confidence, facilities, and customer loyalty